Ceramic-based sodium-ion battery diaphragm with high ion mobility and preparation method of ceramic-based sodium-ion battery diaphragm
Through the use of modified polyacrylonitrile matrix and modified alumina coating materials, the problems of uneven ion conductivity and thermal stability of the sodium ion battery separator are solved, and high ion mobility and excellent high temperature resistance are achieved.
Patent Information
- Application Number
- CN202411819840.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The ionic conductivity of the existing sodium ion battery separators, the dispersion, thermal stability and mechanical properties of ceramic particles need to be further improved.
The modified polyacrylonitrile matrix and modified alumina coating material are used to improve the porosity and hydrophilicity of the ceramic separator through casting treatment and modification reaction, and enhance its wettability with the electrolyte and high temperature resistance.
The high ion mobility, porosity, liquid retention and thermal stability of the ceramic sodium-based ion battery separator are significantly improved, and its overall performance is optimized.
Smart Images

Figure BDA0005182833320000111
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of battery diaphragm materials, and in particular to a ceramic-based sodium ion battery diaphragm with high ion mobility and a preparation method thereof. Background Art
[0002] As a storage technology with great potential, sodium-ion batteries have broad application prospects in the field of large-scale energy storage due to their advantages such as low cost, abundant resources and environmental protection. Compared with lithium-ion batteries, sodium-ion batteries have abundant and widely distributed sodium resources, which can reduce dependence on scarce resources. Therefore, they are regarded as an important direction in future energy storage technology.
[0003] However, although the positive and negative electrode materials of sodium-ion batteries have always been the focus of research, the diaphragm as the core component of the battery is often overlooked. In sodium-ion batteries, the diaphragm plays a vital role. It can not only effectively isolate the positive and negative electrodes of the battery, prevent short circuits and internal decomposition of the battery, but also store electrolytes and provide ion migration channels. The performance of the diaphragm directly determines the efficiency, life and safety of the battery. Therefore, improving the performance of the diaphragm has become one of the key factors in improving the overall performance of sodium-ion batteries.
[0004] Ceramic-based sodium-ion battery separator is a key component used in sodium-ion batteries. It uses ceramic materials or ceramic composite materials as the main materials to improve the performance, safety and durability of the battery. Compared with traditional polymer-based separators, ceramic-based battery separators have better thermal stability, mechanical strength and ionic conductivity.
[0005] The working principle of sodium-ion batteries is similar to that of lithium-ion batteries. The main function of the separator is to provide a stable ion channel to prevent the positive and negative electrodes from directly contacting and short-circuiting, and to ensure that the sodium ions in the battery can migrate efficiently. Since the ionic radius of sodium ions is larger than that of lithium ions, higher requirements are placed on the separator material. Ceramic-based sodium-ion battery separators usually use composite materials of ceramic materials and polymer-based materials (such as polyethylene, polypropylene, etc.), which not only retain the high-temperature stability and ionic conductivity of ceramic materials, but also improve the mechanical strength and flexibility to meet different manufacturing process requirements.
[0006] Although ceramic-based diaphragms can provide better ionic conductivity through composite material design, the uneven distribution of ceramic particles may cause local uneven ionic conductivity, which will affect the overall performance of the battery. The porosity, liquid retention, thermal stability and uneven ionic conductivity of the ceramic particles of the sodium-ion battery diaphragm need to be further improved.
[0007] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention
[0008] The purpose of the present invention is to provide a ceramic-based sodium ion battery separator with high ion mobility and a preparation method thereof, so as to solve the technical problems in the prior art that the ion conductivity of the sodium ion battery separator is uneven, the dispersion of ceramic particles, thermal stability and mechanical properties need to be further improved.
[0009] The object of the present invention can be achieved by the following technical scheme: A method for preparing a ceramic-based sodium ion battery separator with high ion mobility comprises the following steps:
[0010] S1, adding polyacrylonitrile powder, acetone, dimethylformamide, and sodium chloride with a particle size of 155-212 μm into a reaction kettle, stirring, keeping the temperature for reaction for 1-2 hours, and obtaining a polyacrylonitrile matrix by casting treatment;
[0011] S2, adding sodium hydroxide solution and polyacrylonitrile matrix into a reactor for soaking for 2-3 hours, raising the temperature of the reactor to 50-60° C., filtering, washing the filter cake until it is neutral, adding ammonia water and ethanol and soaking for 10-20 minutes to obtain a modified polyacrylonitrile matrix;
[0012] S3. Add modified polyacrylonitrile matrix, modified coating powder and casting liquid into a stirrer and stir. Increase the temperature of the stirrer to 170-200°C and keep the temperature for 2-4 hours. Degassing and film scraping are performed. Post-processing is performed to obtain a high-mobility ceramic diaphragm.
[0013] Furthermore, in step S1, the amount ratio of polyacrylonitrile powder, sodium chloride, acetone and dimethylformamide is 50-70g:14-30g:150-210mL:350-490mL, the stirring rate is 1000r / min; the stirring temperature is 60-70°C; the casting treatment includes, after the reaction is completed, pouring the mixed solution into a casting machine, placing the cast film after the casting treatment in a low-temperature freezer for cooling for 30 minutes, moving it to a deionized water bath for 24 hours, and placing it in a freeze dryer for drying for 24 hours, with a steel knife speed of 99um / s and a scraping gap of 500μm to obtain a polyacrylonitrile matrix.
[0014] Furthermore, in step S2, the sodium hydroxide solution, polyacrylonitrile matrix, ammonia water, and ethanol solution are used in a ratio of 800-1000 mL: 200-500 g: 5-10 mL: 80-100 mL, the concentration of the sodium hydroxide solution is 8%, and the soaking is performed for 1-2 hours to obtain a modified polyacrylonitrile matrix.
[0015] The reaction mechanism of modified polyacrylonitrile is:
[0016] Sodium hydroxide will react nucleophilically with the cyano group in the polyacrylonitrile molecule, causing the cyano group to be hydrolyzed and converted into a carboxylate (-COO-) group. The cyano group of polyacrylonitrile is replaced by a carboxylate. High concentrations of sodium hydroxide can cause the cracking of polyacrylonitrile. Under high temperature conditions, the molecular chain of polyacrylonitrile breaks to generate small molecular compounds, which can increase its chemical reactivity. The addition of ethanol reduces the viscosity of the reaction system, promotes the contact between sodium hydroxide and polyacrylonitrile molecules, and helps to improve the efficiency of the reaction. The addition of ammonia water causes the cyano group (-CN) in the polyacrylonitrile molecule to be replaced by the amino group (-NH2) in the ammonia water, thereby making polyacrylonitrile have higher hydrophilicity, electrophilicity and chemical reactivity, which can enhance its compatibility with other substances and better combine with other fillers, thereby increasing its plasticity and changing its conductive and chemical properties.
[0017] Further, in step S3, the modified coating powder is processed by the following steps:
[0018] A1. Add nano-alumina, triethoxysilane and ethanol into a magnetic stirrer and stir. Raise the stirring temperature to 50-70°C, perform ultrasonic dispersion for 15-16h, condense and reflux under nitrogen atmosphere, centrifuge, wash the alumina precipitate with ethanol for 3-5 times, and perform post-treatment to obtain dispersed alumina.
[0019] A2. Add dispersed alumina and acetic acid into a magnetic stirrer and stir. Raise the stirring temperature to 60-80°C and keep the reaction warm for 11-13 hours. Condensate and reflux under a nitrogen atmosphere. Centrifuge and precipitate the alumina with deionized water until it is neutral. Post-treat to obtain modified alumina.
[0020] Furthermore, in step A1, the dosage ratio of nano-alumina, triethoxysilane and ethanol is 100-200g:100-200g:3000-5000mL, the particle size of alumina is 400-500nm, the concentration of ethanol solution is 20%, the stirring rate is 4000-5000r / min, the centrifugal separation rate is 8000r / min, and the post-treatment includes adding the nano-alumina powder into a vacuum drying oven and drying it to constant weight to obtain dispersed alumina.
[0021] Furthermore, in step A2, the ratio of dispersed alumina to acetic acid is 100-200g:1000-2000mL, the concentration of acetic acid is 0.1mol / L, the stirring rate is 4000-5000r / min, the centrifugal separation rate is 8000r / min, and the post-treatment includes adding nano alumina powder into a vacuum drying oven and drying to constant weight to obtain modified alumina.
[0022] The reaction mechanism of modified alumina is:
[0023] The modified alumina is physically adsorbed to the surface of the modified polyacrylonitrile matrix through van der Waals force and electrostatic force. The physical adsorption does not change the chemical structure of the polyacrylonitrile matrix, but it will enhance the ability of the surface to adhere to alumina. The carboxyl group (-COOH) on the surface of the modified alumina can react with the amino group (-NH2) on the polyacrylonitrile chain to form an amide bond, and react with the cyanide group in the polyacrylonitrile to generate an amino compound. This chemical bonding method enhances the bonding force between the alumina and the polyacrylonitrile matrix, improves the hardness and tensile strength of the composite material, and the high temperature stability of the modified alumina improves the high temperature resistance of the non-woven fabric.
[0024] Furthermore, in step S3, the modified polyacrylonitrile matrix, modified coating powder, and base liquid are used in a ratio of 180-200g:1.8-2g:1000-1500mL, dimethylacetamide and dimethyl phthalate are mixed evenly in a volume ratio of 1:1 to obtain a casting liquid, and post-treatment includes quenching the membrane in a water bath until the membrane is completely solidified, adding an ethanol solution with a concentration of 50% and soaking for 35-45h, the water bath quenching temperature is 15-25°C, and drying at room temperature to obtain a high-mobility ceramic diaphragm.
[0025] The present invention also provides a ceramic-based sodium ion battery separator with high ion mobility. The ceramic-based sodium ion battery separator with high ion mobility is prepared according to the preparation method of the ceramic-based sodium ion battery separator with high ion mobility.
[0026] The present invention has the following beneficial effects:
[0027] 1. Polyacrylonitrile has the advantages of high thermal stability, biosafety, degradability, and high solubility. The modified polyacrylonitrile matrix is used as the composite diaphragm substrate, and the chemical functional groups on the diaphragm matrix interface are optimized to enhance its chemical stability in conventional sodium-ion battery electrolytes. The modified polyacrylonitrile matrix has a porous network structure and good affinity for the electrolyte, with a contact angle of 0° with common electrolytes; it can effectively improve the porosity and hydrophilicity of sodium-ion-based ceramic diaphragm materials, thereby improving their porosity and liquid retention performance.
[0028] 2. Adding modified alumina coating material to the modified polyacrylonitrile matrix for surface coating can not only effectively retain the original characteristics of the base film, but also significantly improve the wettability of the diaphragm with the electrolyte and enhance the temperature resistance of the diaphragm. The surface energy of nano-alumina particles is relatively high. When treated with alkane coupling agents, one end of the particles combines with the hydroxyl group on the surface of alumina and the other end reacts with the dispersion medium, thereby enhancing the inorganic-organic interface effect. In addition, the silane coupling agent is easily hydrolyzed, and the cross-linking density between the nano-alumina particles and the matrix increases, thereby increasing the glass transition temperature of the nano-composite material. In addition, the modified polyacrylonitrile diaphragm exhibits excellent flexibility and does not shrink after being kept at 160°C for 5 hours, showing good heat resistance. This can improve the high temperature resistance and conductivity of the sodium ion-based ceramic diaphragm material, thereby improving its thermal shrinkage performance and conductivity. DETAILED DESCRIPTION
[0029] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] Example 1
[0031] This embodiment provides a method for preparing a ceramic-based sodium ion battery separator with high ion mobility, comprising the following steps:
[0032] S1. Preparation of polyacrylonitrile matrix
[0033] Weigh: 500g of acetone polyacrylonitrile powder, 1500mL of dimethylformamide, 3500mL of acetone, and 140g of sodium chloride, add them into a reactor, stir for 1h, and the stirring rate is 1000r / min; the stirring temperature is 60°C; the casting treatment includes: after the reaction is completed, pouring the mixed solution into a casting machine, placing the cast film after the casting treatment in a low-temperature freezer to cool for 30min, moving it to a deionized water bath for 24h, and placing it in a freeze dryer to dry for 24h, with a steel knife speed of 99um / s and a scraping gap of 500μm to obtain a polyacrylonitrile matrix.
[0034] S2. Preparation of modified polyacrylonitrile matrix
[0035] Weigh: 800 mL of 8 wt% sodium hydroxide solution and 200 g of polyacrylonitrile matrix, add them into a reactor for soaking for 2 hours, raise the temperature of the reactor to 50°C, filter, wash the filter cake until it is neutral, add 50 mL of ammonia water and 800 mL of ethanol, soak for 10 minutes, and obtain a modified polyacrylonitrile matrix.
[0036] S3. Preparation of dispersed alumina
[0037] Weigh: 100 g of nano-alumina with a particle size of 400-500 nm, 100 g of triethoxysilane, and 3000 mL of 20 vol% ethanol, add into a magnetic stirrer and stir, set the stirring speed to 4000-5000 r / min, increase the stirring temperature to 50°C, ultrasonically disperse for 1 h, magnetically stir for 15 h, condense and reflux under a nitrogen atmosphere, centrifuge at a centrifugal separation rate of 8000 r / min to obtain an alumina precipitate, wash the alumina precipitate with ethanol 3-5 times, filter, transfer the filter cake to a vacuum drying oven at a temperature of 90°C, and dry to constant weight to obtain dispersed alumina.
[0038] S4. Preparation of modified alumina
[0039] Weigh: 100 g of dispersed alumina and 1000 mL of acetic acid, add them into a magnetic stirrer and stir, raise the stirring temperature to 60°C, keep the reaction warm for 11 hours, condense and reflux under a nitrogen atmosphere, centrifuge, precipitate and wash the alumina with deionized water until it is neutral, the acetic acid concentration is 0.1 mol / L, the stirring rate is 4000-5000 r / min, the centrifugal separation rate is 8000 r / min, and the post-treatment includes adding nano alumina powder into a vacuum drying oven and drying to constant weight to obtain modified alumina.
[0040] S5. Preparation of high mobility ceramic diaphragm
[0041] Mix dimethylacetamide and dimethyl phthalate in a volume ratio of 1:1 to obtain a film casting solution;
[0042] Weigh: 180g of modified polyacrylonitrile matrix, 1.8g of modified coating powder, and 1000mL of casting liquid, add into a stirrer and stir, raise the temperature of the stirrer to 170°C, keep warm for 4h, degas and scrape the film, quench the film in a water bath until the film is completely solidified, add 50% ethanol solution and soak for 35h, the water bath quenching temperature is 15°C, dry at room temperature, and obtain a high-mobility ceramic diaphragm.
[0043] Example 2
[0044] This embodiment provides a method for preparing a ceramic-based sodium ion battery separator with high ion mobility, comprising the following steps:
[0045] S1. Preparation of polyacrylonitrile matrix
[0046] Weigh: 600g of acetone polyacrylonitrile powder, 1800mL of dimethylformamide, 4200mL of acetone and 200g of sodium chloride are added into a reactor, and stirred for 1.5h at a stirring rate of 1000r / min; the stirring temperature is 65°C; the casting treatment includes: after the reaction is completed, pouring the mixed solution into a casting machine, placing the cast film after the casting treatment in a low-temperature freezer for cooling for 30min, moving it to a deionized water bath for 24h, and placing it in a freeze dryer for drying for 24h, with a steel knife speed of 99um / s and a scraping gap of 500μm to obtain a polyacrylonitrile matrix.
[0047] S2. Preparation of modified polyacrylonitrile matrix
[0048] Weigh: 900 mL of 8 wt% sodium hydroxide solution and 350 g of polyacrylonitrile matrix, add them into a reactor and soak them for 2.5 hours. The temperature of the reactor is raised to 50°C, filtered, and the filter cake is washed until neutral. 90 mL of ammonia water and 900 mL of ethanol are added and soaked for 15 minutes to obtain a modified polyacrylonitrile matrix.
[0049] S3. Preparation of dispersed alumina
[0050] Weigh: 150 g of nano-alumina with a particle size of 400-500 nm, 150 g of triethoxysilane, and 4000 mL of 20 vol% ethanol, add into a magnetic stirrer and stir, raise the stirring temperature to 60°C, ultrasonically disperse for 2 h, magnetically stir for 15 h, condense and reflux under a nitrogen atmosphere, centrifuge at a centrifugal separation rate of 8000 r / min to obtain an alumina precipitate, wash the alumina precipitate with ethanol 3-5 times, filter, transfer the filter cake to a vacuum drying oven at a temperature of 90°C, and dry to constant weight to obtain dispersed alumina.
[0051] S4. Preparation of modified alumina
[0052] Weigh: 150 g of dispersed alumina and 1500 mL of acetic acid, add them into a magnetic stirrer and stir, raise the stirring temperature to 70°C, keep the reaction warm for 12 hours, condense and reflux under a nitrogen atmosphere, centrifuge, precipitate and wash the alumina with deionized water until it is neutral, the acetic acid concentration is 0.1 mol / L, the stirring rate is 4500 r / min, the centrifugal separation rate is 8000 r / min, and the post-treatment includes adding nano alumina powder into a vacuum drying oven and drying to constant weight to obtain modified alumina.
[0053] S5. Preparation of high mobility ceramic diaphragm
[0054] Mix dimethylacetamide and dimethyl phthalate in a volume ratio of 1:1 to obtain a film casting solution;
[0055] Weigh: 190g of modified polyacrylonitrile matrix, 2g of modified coating powder, and 1200mL of casting liquid, add into the stirrer and stir, raise the temperature of the stirrer to 190°C, keep warm for 5h, degas and scrape the film, quench the film in a water bath until the film is completely solidified, add 50% ethanol solution and soak for 40h, the water bath quenching temperature is 20°C, dry at room temperature, and obtain a high-mobility ceramic diaphragm.
[0056] Example 3
[0057] This embodiment provides a method for preparing a ceramic-based sodium ion battery separator with high ion mobility, comprising the following steps:
[0058] S1. Preparation of polyacrylonitrile matrix
[0059] Weigh: 700g of acetone polyacrylonitrile powder, 2100mL of dimethylformamide, 4900mL of acetone and 300g of sodium chloride are added into a reactor, and stirred for 2h at a stirring rate of 1000r / min; the stirring temperature is 70°C; the casting treatment includes: after the reaction is completed, pouring the mixed solution into a casting machine, placing the cast film after the casting treatment in a low-temperature freezer to cool for 30min, moving it to a deionized water bath for 24h, and placing it in a freeze dryer to dry for 24h, with a steel knife speed of 99um / s and a scraping gap of 500μm to obtain a polyacrylonitrile matrix.
[0060] S2. Preparation of modified polyacrylonitrile matrix
[0061] Weigh: 1000 mL of 8 wt% sodium hydroxide solution and 500 g of polyacrylonitrile matrix are added to a reactor for soaking for 3 hours. The temperature of the reactor is raised to 60°C, filtered, and the filter cake is washed until neutral. 100 mL of ammonia water and 1000 mL of ethanol are added and soaked for 20 minutes to obtain a modified polyacrylonitrile matrix.
[0062] S3. Preparation of dispersed alumina
[0063] Weigh: 200 g of nano-alumina with a particle size of 400-500 nm, 200 g of triethoxysilane, and 5000 mL of 20 vol% ethanol, add into a magnetic stirrer and stir, raise the stirring temperature to 70°C, ultrasonically disperse for 3 h, magnetically stir for 15 h, condense and reflux under a nitrogen atmosphere, centrifuge at a centrifugal separation rate of 8000 r / min to obtain an alumina precipitate, wash the alumina precipitate with ethanol 3-5 times, filter, transfer the filter cake to a vacuum drying oven at a temperature of 90°C, and dry to constant weight to obtain dispersed alumina.
[0064] S4. Preparation of modified alumina
[0065] Weigh: 200 g of dispersed alumina and 2000 mL of acetic acid, add them into a magnetic stirrer and stir, raise the stirring temperature to 80°C, keep the reaction warm for 13 hours, condense and reflux under a nitrogen atmosphere, centrifuge, precipitate and wash the alumina with deionized water until it is neutral, the acetic acid concentration is 0.1 mol / L, the stirring rate is 5000 r / min, the centrifugal separation rate is 8000 r / min, and the post-treatment includes adding nano alumina powder into a vacuum drying oven and drying to constant weight to obtain modified alumina.
[0066] S5. Preparation of high mobility ceramic diaphragm
[0067] Mix dimethylacetamide and dimethyl phthalate in a volume ratio of 1:1 to obtain a film casting solution;
[0068] Weigh: 200g of modified polyacrylonitrile matrix, 2g of modified coating powder, and 1500mL of casting liquid, add into the stirrer and stir, increase the temperature of the stirrer to 200℃, keep warm for 6h, degas and scrape the film, quench the film in a water bath until the film is completely solidified, add 50% ethanol solution and soak for 45h, the water bath quenching temperature is 25℃, dry at room temperature, and obtain a high-mobility ceramic diaphragm.
[0069] Comparative Example 1
[0070] The difference between this comparative example and Example 3 is that in step S2, the polyacrylonitrile is not modified.
[0071] Comparative Example 2
[0072] The difference between this comparative example and Example 3 is that in step S3, the nano-alumina is not modified.
[0073] Comparative Example 3
[0074] The difference between this comparative example and Example 3 is that in step S3, no ammonia water is added.
[0075] Performance Test:
[0076] The reference standard GB / T18287-2013 "General Specification for Lithium-ion Batteries" specifies the porosity, thermal shrinkage, thermal stability, and conductivity indicators of lithium battery separators;
[0077] Determination of thermal shrinkage rate of diaphragm: refer to the formula Q(%) = (S0-S) / S0×100%, where Q represents the thermal shrinkage rate of the diaphragm, S0 and S are the areas of the diaphragm before and after treatment at high temperature; Determination of liquid absorption rate of diaphragm: refer to the formula H(%) = (W-W0) / W0×100%, where η represents the liquid absorption rate of the diaphragm, W0 and W are the weight of the diaphragm before and after immersion in the electrolyte; Determination of porosity of diaphragm: refer to the formula P(%) = (Δm / ρ) / V, where P represents the porosity of the diaphragm, Δm is the weight difference before and after the diaphragm absorbs n-butanol, ρ is the density of n-butanol, and V is the total volume of the diaphragm; Determination of ion diffusion rate of diaphragm: refer to the formula δ = L / (R·S), where δ is the ionic conductivity of the diaphragm, L represents the thickness of the diaphragm, R is the charge transfer resistance of the diaphragm, and S is the area of the gasket. The specific test results are shown in Table 1 below.
[0078] Table 1-Performance test data of the sample
[0079]
[0080] Data Analysis:
[0081] A comparative analysis of the data of Examples 1-3 and Comparative Examples 1-3 shows that the porosity of the ceramic-based sodium ion battery separator with high ion mobility prepared by the present invention can reach 52.34%, the liquid retention rate can reach 98.56%, and the ion conductivity can reach 1.057 mS / cm, and all performance parameters are better than those of the comparative example.
[0082] Compared with Examples 1-3, the porosity, liquid retention rate, ionic conductivity and thermal shrinkage rate of Comparative Example 1 are reduced, indicating that the modification of the polyacrylonitrile matrix can effectively improve the porosity and chemical resistance of the sodium ion-based ceramic diaphragm material, thereby improving its porosity and liquid retention performance.
[0083] Compared with Examples 1-3, the porosity, liquid retention rate, ionic conductivity and thermal shrinkage rate of Comparative Example 2 are reduced, indicating that the modification of alumina can effectively improve the crosslinking density between nano-alumina particles and the matrix, increase the glass transition temperature of the nano-composite material, and further improve the high temperature resistance of the sodium ion-based ceramic diaphragm material, thereby improving its thermal shrinkage performance.
[0084] Compared with Examples 1-3, the porosity, liquid retention rate, ionic conductivity and thermal shrinkage rate of Comparative Example 3 are reduced, indicating that the addition of ammonia water causes the cyano group (-CN) in the polyacrylonitrile molecule to be replaced by the amino group (-NH2) in the ammonia water, thereby making the polyacrylonitrile have higher hydrophilicity, electrophilicity and chemical reaction activity, effectively improving the liquid retention rate and conductivity of the sodium ion-based ceramic diaphragm material, thereby improving its electrochemical performance.
[0085] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
[0086] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0087] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A method for preparing a ceramic-based sodium ion battery separator with high ion mobility, characterized in that: The following steps are involved: S1, adding polyacrylonitrile powder, acetone, dimethylformamide, and sodium chloride with a particle size of 155-212 μm into a reaction kettle, stirring, keeping the temperature for reaction for 1-2 hours, and obtaining a polyacrylonitrile matrix by casting treatment; S2, adding sodium hydroxide solution and polyacrylonitrile matrix into a reactor for soaking for 2-3 hours, raising the temperature of the reactor to 50-60° C., filtering, washing the filter cake until it is neutral, adding ammonia water and ethanol and soaking for 10-20 minutes to obtain a modified polyacrylonitrile matrix; S3. Add modified polyacrylonitrile matrix, modified coating powder and casting liquid into a stirrer and stir. Increase the temperature of the stirrer to 170-200°C, keep the temperature for 4-6 hours, degas and scrape the film, and then post-treat to obtain a high-mobility ceramic diaphragm.
2. The method for preparing a ceramic-based sodium ion battery separator with high ion mobility according to claim 1, characterized in that: In step S1, the amount ratio of polyacrylonitrile powder, sodium chloride, acetone and dimethylformamide is 50-70g:14-30g:150-210mL:350-490mL, the stirring rate is 1000r / min, and the stirring temperature is 60-70°C; the casting treatment includes, after the reaction is completed, pouring the mixed solution into a casting machine, placing the cast film after the casting treatment in a low-temperature freezer for cooling for 30min, moving it to a deionized water bath for 24h, and placing it in a freeze dryer for drying for 24h, with a steel knife speed of 99um / s and a scraping gap of 500μm to obtain a polyacrylonitrile matrix.
3. The method for preparing a ceramic-based sodium ion battery separator with high ion mobility according to claim 1, characterized in that: In step S2, the sodium hydroxide solution, polyacrylonitrile matrix, ammonia water, and ethanol solution are used in a ratio of 800-1000 mL: 200-500 g: 5-10 mL: 80-100 mL, the concentration of the sodium hydroxide solution is 8%, and the soaking is performed for 1-2 hours to obtain a modified polyacrylonitrile matrix.
4. The method for preparing a ceramic-based sodium ion battery separator with high ion mobility according to claim 1, characterized in that: In step S3, the modified coating powder is processed by the following steps: A1. Add nano-alumina, triethoxysilane and ethanol into a magnetic stirrer and stir. Raise the stirring temperature to 50-70°C, perform ultrasonic dispersion for 15-17h, condense and reflux under nitrogen atmosphere, centrifuge, wash the alumina precipitate with ethanol for 3-5 times, and perform post-treatment to obtain dispersed alumina. A2. Add dispersed alumina and acetic acid into a magnetic stirrer and stir. Raise the stirring temperature to 60-80°C and keep the reaction warm for 11-13 hours. Condensate and reflux under a nitrogen atmosphere. Centrifuge and precipitate the alumina with deionized water until it is neutral. Post-treat to obtain modified alumina.
5. The method for preparing a ceramic-based sodium ion battery separator with high ion mobility according to claim 4, characterized in that: In step A1, the dosage ratio of nano-alumina, triethoxysilane and ethanol is 100-200g:100-200g:3000-5000mL, the diameter of alumina particles is 400-500nm, the concentration of ethanol solution is 20%, the stirring rate is 4000-5000r / min, the centrifugal separation rate is 8000r / min, and the post-treatment includes adding the nano-alumina powder into a vacuum drying oven and drying it to constant weight to obtain dispersed alumina.
6. The method for preparing a ceramic-based sodium ion battery separator with high ion mobility according to claim 4, characterized in that: In step A2, the ratio of dispersed alumina to acetic acid is 100-200g:1000-2000mL, the concentration of acetic acid is 0.1mol / L, the stirring rate is 4000-5000r / min, the centrifugal separation rate is 8000r / min, and the post-treatment includes adding nano alumina powder into a vacuum drying oven and drying to constant weight to obtain modified alumina.
7. The method for preparing a ceramic-based sodium ion battery separator with high ion mobility according to claim 1, characterized in that: In step S3, the modified polyacrylonitrile matrix, modified coating powder, and base liquid are used in a ratio of 180-200g:1.8-2g:1000-1500mL, dimethylacetamide and dimethyl phthalate are mixed evenly in a volume ratio of 1:1 to obtain a casting liquid, and post-treatment includes quenching the membrane in a water bath until the membrane is completely solidified, adding an ethanol solution with a concentration of 50% and soaking for 35-45h, the water bath quenching temperature is 15-25°C, and drying at room temperature to obtain a high-mobility ceramic diaphragm.
8. A ceramic-based sodium ion battery separator with high ion mobility, characterized in that: The ceramic-based sodium-ion battery separator with high ion mobility is prepared according to the method for preparing the ceramic-based sodium-ion battery separator with high ion mobility according to any one of claims 1 to 7.